1998
DOI: 10.1007/s002130050648
|View full text |Cite
|
Sign up to set email alerts
|

Differential responsiveness to cocaine in C57BL/6J and DBA/2J mice

Abstract: The present study compared cocaine-induced hyperlocomotion and cocaine i.v. self-administration in DBA/2J and C57BL/6J mice. In the locomotor activity experiment, these strains were tested for hyperlocomotion after i.p. cocaine injection (0-60.0 mg/kg), using a Digiscan Animal Activity Monitoring System. In the cocaine i.v. self-administration experiment, they were compared for their ability to acquire and maintain cocaine self-administration in operant chambers with levers as the manipulanda. Animals were fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
1

Year Published

2001
2001
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 0 publications
5
47
1
Order By: Relevance
“…Specifically, individuals with low trait anxiety may need more stimulation to achieve the same rewarding experience than individuals with high trait anxiety (Figure 10). Accordingly, evidence from several previous studies show that nonemotional inbred strains such as C57BL/6 readily self-administer high doses of cocaine (Carney et al 1991;Grahame et al 1995;Rocha et al 1998), and we have shown qualitative and quantitative differences in self-administration between BALB/cByJ and C57BL/6 x SJL hybrid mice (Deroche et al 1997).…”
Section: Clinical Relevance: a Mechanism Underlying Vulnerability To supporting
confidence: 58%
See 2 more Smart Citations
“…Specifically, individuals with low trait anxiety may need more stimulation to achieve the same rewarding experience than individuals with high trait anxiety (Figure 10). Accordingly, evidence from several previous studies show that nonemotional inbred strains such as C57BL/6 readily self-administer high doses of cocaine (Carney et al 1991;Grahame et al 1995;Rocha et al 1998), and we have shown qualitative and quantitative differences in self-administration between BALB/cByJ and C57BL/6 x SJL hybrid mice (Deroche et al 1997).…”
Section: Clinical Relevance: a Mechanism Underlying Vulnerability To supporting
confidence: 58%
“…The first observation resulting from the present experiment is that BALB/cByJ mice exhibited intravenous cocaine self-administration behavior when using a low dose known to be ineffective in several other strains (Carney et al 1991;Grahame et al 1995;Deroche et al 1997;Rocha et al 1998). The use of a habituation session allowing the mice to explore the apparatus freely before cocaine was made available may have favored the expression of this behavior.…”
Section: Intravenous Cocaine Self-administration In Balb/cbyjmentioning
confidence: 74%
See 1 more Smart Citation
“…This association, however, may depend on the drug tested. For example, although several laboratories have shown that DBA/2J mice show enhanced cocaine-evoked locomotion compared to C57BL/6J (Rocha et al, 1998;Phillips et al, 1998), a microdialysis study found no difference in the magnitude of cocaine-evoked DA levels in the nucleus accumbens between these two mouse strains (He and Shippenberg, 2000). The results obtained on ETOH-evoked DA levels in the nucleus accumbens are supported by a previous in vitro study in which ETOH-stimulated DA cell firing in ventral tegmental area slices of DBA/2J mice was similar to that in C57BL/6J mice (Brodie and Appel, 2000), at least at the same ETOH concentrations used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacogenetic studies in C57 and DBA mice support the above-mentioned hypothesis as these mouse lines exhibit parallel differential sensitivity to the locomotorstimulant effects of both ethanol and cocaine, with C57 mice exhibiting less locomotion to both drugs (Rocha et al, 1998;Tolliver and Carney, 1995;Womer et al, 1994). However, this is not the case with all mouse lines.…”
Section: Introductionmentioning
confidence: 85%